Solar power optimiser for smart hybrid - Teng, Medwin Tong Wei. (2013)
As the world becomes increasingly reliant on energy, conventional power production using non-renewable resources is escalating at an tremendous rate in order to satisfy the demand. In face of surging prices and environmental concerns, the focus has shifted to alternative renewable solutions to ease the strain. One of the solutions, photovoltaic technology, is one of the most popular and widely researched system in renewable power production today.